The Triple Spar campaign: Model tests of a 10MW floating wind turbine with waves, wind and pitch control. (October 2017) - Bredmose, H.; Lemmer, F.; Borg, M.; Pegalajar-Jurado, A.; Mikkelsen, R.F.; Larsen, T. Stoklund; Fjelstrup, T.; Yu, W.; Lomholt, A.K.; Boehm, L.; Armendariz, J. Azcona
Abstract: Results of a test campaign for a floating wind turbine in simultaneous wind and wave forcing at scale 1:60 are presented. The floater is the Triple Spar floater, a hybrid between a spar buoy and a semi submersible tri-floater, tested here for the first time. The turbine is a model scale version of the DTU 10 MW reference wind turbine, which, also for the first time, is tested with active blade pitch control. The tests focus on the effects of aerodynamic damping and interaction effects between the wind forcing, wave forcing and the blade pitch control algorithm. Special focus is devoted to the instability of the platform pitch natural mode, that can occur if a standard land-based controller is applied. Results of three control strategies are reported: Fixed blade pitch, a standard land-based controller, and a tuned controller designed to eliminate the instability. Special rotor ID tests were carried out to characterize the rotor and identify the control parameters. Results for regular waves, focused wave groups, a wind-only test and irregular waves are presented in terms of time series, power spectra and exceedance probability plots. Among the key results are the wind-induced steady offset of floater pitch and surge and the aerodynamic damping of the floater pitch motion. Further, a clear example of the onset of unstable motion at the platform natural pitch frequency is provided along with a detailed analysis of the dynamic response for irregular wave conditions with the three control strategies. The paper ends with the first results of numerical re-modelling of the response for a waves-only test. A good match is found, thus encouraging further work in this direction.